2017
DOI: 10.1021/acsphotonics.7b00544
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Anisotropic Dielectric Metasurfaces for Ultrafast Nanophotonics

Abstract: We report on the broadband transient optical response of anisotropic, amorphous silicon nanobricks that exhibit Mie-type resonances. A quantitative model is developed to identify and disentangle the three physical processes that govern the ultrafast changes of the nanobrick optical properties, namely, two-photon absorption, free-carrier relaxation, and lattice heating. We reveal a set of operating windows where ultrafast all-optical modulation of transmission is achieved with full return to zero in 20 ps. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 44 publications
0
55
0
Order By: Relevance
“…Because of their distinct properties, RDNs have been proposed for high‐harmonic generation, photonic topological insulators, boosting the luminescence from quantum emitters such as NV‐centers in nanodiamonds, quantum dots, perovskites, dye molecules, and carbon nanotubes . In addition, resonant dielectric nanostructures have been used for scattering engineering, ultrafast switchers and modulators, optical interconnections on a chip, light trapping structures, colored metasurfaces, and enhanced Raman scattering . Interesting photonic phenomena such as Fano resonances, Purcell effect, and strong coupling have been shown in dielectric nanostructures as well.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their distinct properties, RDNs have been proposed for high‐harmonic generation, photonic topological insulators, boosting the luminescence from quantum emitters such as NV‐centers in nanodiamonds, quantum dots, perovskites, dye molecules, and carbon nanotubes . In addition, resonant dielectric nanostructures have been used for scattering engineering, ultrafast switchers and modulators, optical interconnections on a chip, light trapping structures, colored metasurfaces, and enhanced Raman scattering . Interesting photonic phenomena such as Fano resonances, Purcell effect, and strong coupling have been shown in dielectric nanostructures as well.…”
Section: Introductionmentioning
confidence: 99%
“…The change of the permittivity due to the FC response can be described using the Drude model asΔεFC=Ne–he2moptε0(ω2+iωτnormald1)=ωnormalp2ω2+iωτnormald1where ε 0 is the permittivity of vacuum; e is the electron charge; and ω is the angular frequency of THz waves. ωnormalp=Ne‐he2/ε0mopt is the plasma frequency, mopt=0.15 mnormale and τ d = 80 fs are given above.…”
Section: Resultsmentioning
confidence: 99%
“…This thermo‐optic effect of Si nanostructures has been utilized to realize spatial light modulation around the communication wavelengths at frequencies up to 10 kHz . On the other hand, optical carrier injection provides a more attractive approach for achieving response tuning of dielectric metasurfaces in an efficient manner by using femtosecond (fs) laser pulses that lead to ultrafast free carrier density change in semiconductors as well as other possible physical processes, such as two‐photon absorption (TPA) and lattice heating . Exploiting the ultrafast TPA process, Shcherbakov et al have identified a 65 fs long transmission switching effect in a hydrogenated amorphous silicon (a‐Si:H) metasurface around the magnetic Mie resonance of the nanodisk resonators.…”
Section: Tuning Dielectric Metasurfaces With Variable Constituent Promentioning
confidence: 99%